Post-fire juvenile period of plants in south-west Australia forets and implications for fire management - Burrows, N.; Wardell-Johnson, Grant; Ward, B. (Royal Society of Western Australia, 2008)
Regular prescribed burning to manage the accumulation of flammable live and dead vegetation(fuel) is a strategy for ameliorating wildfire impacts in fire-prone environments. The intervalbetween prescribed fires needs to be sufficient to manage fuel accumulation but it should also beecologically acceptable. Time to first flowering after fire (juvenile period) is a biological indicatorthat can be used to guide minimum intervals between fires to conserve plant diversity. A survey of639 plant species in forests and associated ecosystems of south-west Western Australian revealedthat 97% of understorey species reached flowering age within 3 years of fire and all speciesreached flowering age within 5 years of fire. Within species variation was evident, with plants atthe drier end of their range taking longer to reach flowering age. Fire sensitive plants, beingobligate seeder species with longer juvenile periods (> 3 years), mostly occurred in low rainfallzones so took longer to mature, or in habitats that were less prone to fire because they remainedmoist for a longer period or because surface fuels were inherently sparse and discontinuous. Dueto uncertainty about the reproductive biology and seed bank dynamics of most of the flora, werecommend that the conservative minimum interval between fires that are lethal to fire sensitiveplants is about twice the juvenile period of the slowest maturing species in the community.Occasional landscape fires at shorter intervals would be ecologically acceptable only if these fireswere of a sufficiently low intensity as to not kill plants with long juvenile periods, or were patchyand did not burn the habitats in which they occur.